Integrated Approach to Learning (On the Example of a Private Institution “School of the Free and Responsive”) - Pylypiv, Olha (Journal of Vasyl Stefanyk Precarpathian National University, 2020)
The current stage of reforming the Ukrainian national school is characterized by a complication of the сontent of education, an increase in the amount of information and a reduction in the time allotted for its learning. Today, the development of education as a system must be realized through systemic knowledge, which is necessary for forming holistic and systemic thinking. This knowledge can be obtained through the integration of the humanities and fundamental disciplines and should be guided by the global level of science development. This approach contributes to the formation of holistic ideas about the world and a human as a whole. These ideas are outlined by the author in the article. The search for ways to improve the education system at school has helped revive the notion of integration of learning, which is gradually being implemented in primary school practice. The purpose of the article is to analyze the main aspects of an integrated approach to teaching at elementary school and to reveal the pedagogical value of thematic days. At the moment, the main task of education in the 21st century is to improve, develop and shape attention, imagination, thinking and memory. However, in general, today's level of the development of education in Ukraine does not give an opportunity to fully fulfill the function of the key resource of the socio-economic development of the country and increase the welfare of citizens. The prestige of education and science in society remains low nowadays. Today, in Ukraine different legislative and regulatory acts provide the implementation of cardinal changes aimed at “a comprehensive development of a person as a personality and the highest value of society, shaping his or her talents, mental and physical abilities, upbringing high moral qualities, forming the citizens capable of a conscious public choice, enrichment on this basis of intellectual, creative, cultural potential of the nation, raising the educational level of the people, providing the national economy with qualified specialists. Ukraine recognizes education as a priority area of socio-economic, spiritual and cultural development of society” [7, p. 65].